An Assessment of the Critical Success Factors of Microfinance Institutions (MFIs) in Lusaka, Zambia - Nyirenda, Noah David; Mulenga, Anastasia C.; Mwanza, Bupe G. (International Journal of Learning and Development, 2024)
This research focuses on the critical success and failure factors of microfinance institutions (MFIs) in Lusaka, Zambia, addressing a vital aspect of the financial landscape that impacts small businesses and low-income individuals. Despite the positive role of MFIs in providing financial assistance to entrepreneurs, recent closures of six institutions in Zambia underscore the need to understand the factors influencing their success or failure. The problem statement highlights the potential consequences of MFI closures, such as negative impacts on women, increased poverty levels, income inequality, child labor, and barriers to sustainable local economic development. Notably, the study aims to fill a research gap by assessing factors affecting MFIs’ operations in Zambia, particularly those leading to closures, which the Bank of Zambia has not yet addressed or documented. The research objectives are clear and specific, intending to assess both critical failure factors from MFIs that have closed in Lusaka and critical success factors for the functioning of MFIs in the region. Additionally, the study aims to suggest measures to enhance the application of these critical success factors. Moving into the research methodology, an exploratory research design is chosen, providing a foundation for assessing the critical success factors of MFIs in Zambia. The mixed-method approach, incorporating qualitative and quantitative strategies, enhances the comprehensiveness of the study. The target population comprises 29 registered MFIs in Lusaka, and a one-stage cluster sampling technique is applied to select 10 MFIs with 60 key informants. The use of questionnaires for data collection, both open and closed-ended, facilitates the gathering of both qualitative and quantitative information. Ethical considerations are diligently addressed, ensuring informed consent, confidentiality, justice, anonymity, and protection from harm. In the discussion of findings, a demographic analysis reveals important characteristics of the respondent base, emphasizing the predominantly male representation and the prevalence of tertiary education among participants. Objective one focuses on assessing critical failure factors, with limited access to funding, operational efficiency, and limited financial literacy emerging as primary challenges. Objective two delves into critical success factors, highlighting financial stability, marketing strategies, technology adoption, and outreach to the underserved population as significant considerations. Objective three provides insights into measures employed by MFIs, such as technology integration, capacity building, customer-centric approaches, and risk management systems. The recommendations emphasize diversification of funding sources, tailored financial literacy initiatives, operational efficiency optimization, and enhanced community engagement to address identified challenges. In summary, this study contributes valuable insights into the dynamics of MFIs in Lusaka, offering practical recommendations for their sustained success and impact on local communities.